URGENSI PENDIDIKAN POLITIK DAN HUKUM DALAM MEMBANGUN MASYARAKAT DEMOKRATIS - Virly Filia; Alya Haris (Educatus, 2025)
This research discusses the urgency of political and legal education in strengthening democracy in Indonesia, especially in the midst of the rise of corruption, collusion and nepotism practices (KKN) which undermines the integrity of the government system.Using a descriptive qualitative approach, this research analyzes how low political literacy and community legal awareness contribute to the weakness of public participation and supervision of power.Data obtained through literature study of policy documents, anti -corruption reports, and the latest academic literature, which were then analyzed thematically.The results showed that political and legal education in Indonesia is still normative and not yet contextual, so it fails to form critical and active citizens.Transformative education, based on democratic values and legal supremacy, is very necessary to build a society that is able to fight the practice of KKN and demand public accountability.The conclusion of this study confirms that the strengthening of political and legal education must be a national strategic agenda in order to realize substantive democracy and clean governance.